2016
DOI: 10.1038/nature19055
|View full text |Cite
|
Sign up to set email alerts
|

Operation of a homeostatic sleep switch

Abstract: Sleep disconnects animals from the external world, at considerable risks and costs that must be offset by a vital benefit. Insight into this mysterious benefit will come from understanding sleep homeostasis: to monitor sleep need, an internal bookkeeper must track physiological changes that are linked to the core function of sleep1. In Drosophila, a crucial component of the machinery for sleep homeostasis is a cluster of neurons innervating the dorsal fan-shaped body (dFB) of the central complex2,3. Artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
367
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(389 citation statements)
references
References 42 publications
14
367
0
Order By: Relevance
“…The effects of sleep loss depend on the RhoGTPase-activating protein, CROSS-VEINLESS-C (CV-C) whose function also strongly affects baseline sleep (Donlea et al 2014). dFB neurons are inhibited by key arousal promoting dopaminergic neurons via activation of the potassium "leak" current carried by Sandman, a two-pore potassium channel, and the suppression of voltage-gated A-type potassium current likely encoded in part by Sh (Pimentel et al 2016). Although these studies reveal the mechanistic basis for dopaminergic arousal, it remains unclear whether these dopamine-dependent changes are important for homeostatic responses to sleep deprivation.…”
Section: Acetylcholinementioning
confidence: 99%
“…The effects of sleep loss depend on the RhoGTPase-activating protein, CROSS-VEINLESS-C (CV-C) whose function also strongly affects baseline sleep (Donlea et al 2014). dFB neurons are inhibited by key arousal promoting dopaminergic neurons via activation of the potassium "leak" current carried by Sandman, a two-pore potassium channel, and the suppression of voltage-gated A-type potassium current likely encoded in part by Sh (Pimentel et al 2016). Although these studies reveal the mechanistic basis for dopaminergic arousal, it remains unclear whether these dopamine-dependent changes are important for homeostatic responses to sleep deprivation.…”
Section: Acetylcholinementioning
confidence: 99%
“…Regarding the CX, Guo and Ritzmann (2013) have shown that most CX units show an increase in their firing rate prior to the initiation of locomotion, indicating that the CX promotes walking. In addition, monoamines have been found to have an impact on the CX thereby affecting various aspects of sleep regulation in drosophila [34,35]. Finally, injection of the monoamine octopamine in the CX partially restores walking in hypokinetic cockroaches stung by the wasp [36].…”
Section: Resultsmentioning
confidence: 99%
“…It was originally proposed that the dopamine engaged Dop1R1 and a Gs/cAMP-dependent pathway [81,83]. More recently, a (noncanonical, pertussis-toxin-sensitive) Gi/Go-mediated signaling via Dop1R2 was shown to elicit two distinct effects on the postsynaptic neurons of the fan-shaped body, which operate on different time scales: an instant -but transient -hyperpolarization, which was due to stimulation of one or several voltage-activated K+-channels, and an off-state, which relies on the exocytosis of an internal, vesicular store of a two-pore-domain K + -channel; this K2P-channel was termed Sandman [80]. Insertion of Sandman produces a large leak current, which silences the fan-shaped body neurons and thus produces a long-lasting state of wakefulness [80].…”
Section: The Dopaminergic Systemmentioning
confidence: 99%
“…(ii) Sleep regulation in flies relies on the fan-shaped body [62,[80][81][82][83]. Dopamine promotes arousal; the neurons involved are somewhat controversial as are the postsynaptic receptors and signaling mechanisms: a single pair of dopaminergic neurons from PPL1 [81] and/or PPM3 [83] suffices to drive the arousal reaction.…”
Section: The Dopaminergic Systemmentioning
confidence: 99%